DETERMINATION OF FIBER DEVELOPMENT OF LIVER IN PATIENTS WITH TYPE 2 DIABETES MELLITUS ASSOCIATED WITH NON-ALCOHOL FATTY LIVER DISEASE - Павловський, С.А.; Вірстюк, Н.Г. (World of Medicine and Biology, 2018)
According to experts from the three European Professional Associations: European Association for the Study of the Liver (EASL), the European Association for the Study of Diabetes (EASD) and the European Association for the Study of Obesity (EASO), NAFLD is the most common liver disease in countries of Western Europe and covers 17-46% of the adult population. NAFLD at present is not considered as an isolated pathology, and one that is accompanied by a defeat of other organs and systems and can act as a predictor of cardiovascular disease. Therefore, according to the recommendations of the hepatologic associations, an assessment of metabolic disorders and cardiovascular risk is included in the compulsory screening program for patients with NAFLD. The aim of the work was to evaluate the degree of progression of liver fibrosis in patients with type 2 diabetes, depending on the course of NAFLD. The subject of the study was 155 patients with NAFLD, among which 75 persons were allocated without type 2 diabetes (Group I) and 80 persons with subcompensated type 2 diabetes (group II). Among patients in each group, patients with non-alcoholic fatty hepatosis (NAFH) - IA group (n = 53) and ІІА group (n = 46) and nonalcoholic steatohepatitis (NASH) - IB group (n = 22) and ІІB group (n = 32) Diagnosis of NAFLD was established according to the unified clinical protocol "Non-alcoholic steatohepatitis" and an adapted clinical guideline based on the evidence "Non-alcoholic fatty liver disease", according to the recommendations of the European Association for the Study of Liver (EASL), the European Association for the Study Diabetes (EASD), European Association for the Study of Obesity (EASO). Type 2 diabetes was diagnosed according to the unified clinical protocol "Non-alcoholic steatohepatitis", an adapted clinical guideline based on the evidence "Type 2 diabetes", recommendations of the American Association of Diabetics. All patients were given a general-clinical examination (analysis of complaints, medical history, anamnesis of life, objective status), ECG, ultrasound, liver elastography, assessment of functional state of the liver, carbohydrate and fat metabolism, calculation of FIB-4 fibrosis indexes (FibroIndex- 4) and NFS (Non-alcoholic Fatty Liver Disease Fibrosis Score). According to the results of evaluation of liver elastography and index of fibrosis-4 (FIB-4) and fibrosis score in non-alcoholic fatty liver disease (NAFLD) - (NFS), a higher degree of fibrosis was found in the presence of nonalcoholic steatohepatitis (NASH) compared with steatohepatosis (NAGH). It was found that the presence of type 2 diabetes mellitus (diabetes mellitus) contributes to the progression of liver fibrosis in patients with liver inflammatory bowel disease both at the stage of NAFLD and at the stage of NASH by the values of the velocity of the shear wave and the indices of FIB-4 and NFS. In patients with NAFLD in the presence of type 2 diabetes, low fibrosis (F0, F1, F2) was observed in 24 (52.17%) patients, high (F3, F4) in 22 (47.83%) patients; in patients with NASH without diabetes - in 11 (32.35%) and 23 (67.65%) respectively. Determination of stiffness of the liver by the method of elastography, the calculation of indices FIB-4 and NFS contributes to the early detection of fibrotic changes in the parenchyma of the liver, which, in general, makes the expediency of incorporating these methods into the protocol for the examination of patients with diabetes 2-type, combined with NAFLD.